Synthesis and characterization of inorganic perovskite quantum dots (CsPbI3) based thin films for solar cells applications - Khalil, Asad Y.; Rashid, Marzaini; Idris, Muhammad Idzdihar (2023)
Colloidal quantum dots (CQDs) solar cells, which are made of inorganic semiconductor nanomaterials, provide a number of unique characteristics. Particularly inorganic perovskite QDs (CsPbI3 PQDs), owing to the high photovoltaic efficiency and thermal stability of these materials. However, the required phase is α - phase to fabricate devices with high efficiency, but under room temperature, they suffer from formation of undesirable orthorhombic (δ phase) structure, so the thermal and phase instabilities pose challenges in developing CsPbI3. We report an approach to synthesise (CsPbI3 QDs) via hot injection (HI) technique as a promising low temperature and cost-effective method to obtain the desirable stable black phase (α phase) of inorganic perovskite. We observed the appearance of both phases; cubic and orthorhombic structures through measuring photoluminescence (PL) which exhibited PL emission peaks at 500 nm and 700 nm respectively, and the optical bandgap has been measured from UV-visible(UV - Vis) absorption analysis as Eg~ 2.58 eV for the yellow (orthorhombic) phase and Eg~1.77 eV for the black (cubic) phase. Furthermore, X-ray diffraction (XRD), ED-X and field emission - scanning electron microscopy (FE-SEM) analyses have been investigated. It was observed that the local elements of Cs, Pb and I appeared in CsPbI3 thin film. EDX spectrum had no impurity element peaks, other than the presence of an amount of yellow phase (δ phase) in the as - synthesized CsPbI3